Root Microbiome Modulates Plant Growth Promotion Induced by Low Doses of Glyphosate - Dario X. Ramirez-Villacis (American Society for Microbiology, 2020)
ABSTRACT Glyphosate is a commonly used herbicide with a broad action spectrum. However, at sublethal doses, glyphosate can induce plant growth, a phenomenon known as hormesis. Most glyphosate hormesis studies have been performed under microbe-free or reduced-microbial-diversity conditions; only a few were performed in open systems or agricultural fields, which include a higher diversity of soil microorganisms. Here, we investigated how microbes affect the hormesis induced by low doses of glyphosate. To this end, we used Arabidopsis thaliana and a well-characterized synthetic bacterial community of 185 strains (SynCom) that mimics the root-associated microbiome of Arabidopsis. We found that a dose of 3.6 × 10−6 g acid equivalent/liter (low dose of glyphosate, or LDG) produced an ∼14% increase in the shoot dry weight (i.e., hormesis) of uninoculated plants. Unexpectedly, in plants inoculated with the SynCom, LDG reduced shoot dry weight by ∼17%. We found that LDG enriched two Firmicutes and two Burkholderia strains in the roots. These specific strains are known to act as root growth inhibitors (RGI) in monoassociation assays. We tested the link between RGI and shoot dry weight reduction in LDG by assembling a new synthetic community lacking RGI strains. Dropping RGI strains out of the community restored growth induction by LDG. Finally, we showed that individual RGI strains from a few specific phyla were sufficient to switch the response to LDG from growth promotion to growth inhibition. Our results indicate that glyphosate hormesis was completely dependent on the root microbiome composition, specifically on the presence of root growth inhibitor strains. IMPORTANCE Since the introduction of glyphosate-resistant crops, glyphosate has become the most common and widely used herbicide around the world. Due to its intensive use and ability to bind to soil particles, it can be found at low concentrations in the environment. The effect of these remnants of glyphosate in plants has not been broadly studied; however, glyphosate 1,000 to 100,000 times less concentrated than the recommended field dose promoted growth in several species in laboratory and greenhouse experiments. However, this effect is rarely observed in agricultural fields, where complex communities of microbes have a central role in the way plants respond to external cues. Our study reveals how root-associated bacteria modulate the responses of Arabidopsis to low doses of glyphosate, shifting between growth promotion and growth inhibition.